Analisis Penyelidikan Tanah Pada Proyek Pembangunan Service Center Rawa Buaya, Jakarta Barat - Rendi Agustiawan; Alizar Alizar (Publikasi Indonesia, 2025)
Soil investigation is an important step in construction planning to determine soil characteristics and bearing capacity. This study aims to analyze soil conditions at the Rawa Buaya Service Center Building Development Project site, West Jakarta. The study uses soil data based on the results of the Cone Penetration Test (CPT), and Standard Penetration Test (SPT). The data obtained are used to evaluate the soil profile, soil bearing capacity, and other geotechnical parameters relevant to the needs of the foundation design. The methodology used involves collecting primary data through field testing and taking soil samples for laboratory analysis. In addition, secondary data from previous geotechnical reports and geological maps are also used to support the results of the analysis. The results of the study indicate that the soil at the study site consists of layers of clay, silt, and sand with varying bearing capacity values depending on the depth. Based on the study, the results of the comparison of the bearing capacity values of the pile foundation permit for CPT data with a depth of 6m obtained from the Sondir1 (S1) point with the Bagemann method of 52.09 tons, and the Wesley method of 43.68 tons. For Sondir2 (S2) point, the Bagemann method is 54.5 tons, and the Wesley method is 51.95 tons. For Sondir3 (S3) point, the Bagemann method is 61.95 tons, and the Wesley method is 58.2 tons. The bearing capacity value of the pile foundation permit for SPT with the Meyerhof method is 66.98 tons.